The effect of zinc and sodium borate doping on the structural, morphological, optical, electrical and electrochemical properties of PEDOT:PSS thin film electrodes for flexible and transparent supercapacitor applications - Yagci, Ozlem; Arvas, Melih Besir; Yuksel, Sureyya Aydin (ROYAL SOC CHEMISTRY, 2024)
In this study, it is proposed to develop new electrodes for high performance and flexible supercapacitors by doping sodium borate (Na2B4O5(OH)4 center dot 8H2O) (NaB) and zinc borate (Zn3B6O12 center dot 3.5H2O) (ZnB) to poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) for the first time. NaB and ZnB were doped to PEDOT:PSS in different ratios (0, 0.3, 0.6, 1.25 and 2.5 mg ml-1) and coated on glass substrates by a spin coating method, which is a simple and low cost deposition technically. Studies were carried out to determine the structural, electrical, optical and morphological properties of the thin films produced. Electrochemical properties were determined by electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and galvanostatic charge/discharge (GCD) tests. The 2.5 mg ml-1 NaB doped PEDOT:PPS/GCE exhibited 10 times higher capacitance than the undoped PEDOT:PSS electrode material (1.0 V potential range, 0.1 M NaCl electrolyte). This study proposes a new electrode material produced at low cost in one-step for supercapacitor applications with improved electrochemical performance. In this study, for the first time, we propose new electrode materials for transparent and flexible supercapacitors by doping sodium borate (NaB) and zinc borate (ZnB) to poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS).
Keywords: HIGH-PERFORMANCE; HYBRID; Chemistry